Pre-admission qualification and demographic factors of year one national dipoloma students of federal colleges of agriculture as precursors of achievement in mathematics (2011)
Mathematics serves as a strong reinforcement to most courses offered in Federal Colleges of Forestry and Federal Colleges of Animal Health and Production Technology. Despite the importance of mathematics in colleges of agriculture, students' achievement in mathematics courses was not impressive. The observed performance could be explained by students' demographic factors and pre-admission qualification. This study investigated students' demographic factors (sex, age, fathers' highest qualification and occupation as well as mothers' highest qualification and occupation) and pre-admission qualification (senior secondary certificate examination and unified tertiary matriculation examination) as precursors of their cognitive achievement in mathematics. This study adopted correlational approach. Four hundred and four students of the colleges that sat for 2010 UTME and admitted into Federal College of Forestry Ibadan and Federal College of Animal Health and Production Technology Ibadan were used for the study. Data was collected from the colleges using students record files and achievement test in mathematics (difficulty level ranging from 0.4 to 0.5 and reliability coefficient = 0.83). The data was analysed using Frequencies, percentages/ and multiple regression analysis. The result showed that the highest percentage of students, 33.9 per cent scored between 40 and 50 per cent,17.6 per cent failed while only 5.2 per cent scored 70 per cent and above. The independent variables regresses against achievement in mathematics had composite influence on achievement in mathematics (R = .347 and Adjusted R2=0.102; F(8,390) =6.673;P<.05). It was alaso found that only UTME scores (β=.155;t=2.984; p<0.05) and mothers' occupation(β=-.176:t=-3.528: p<0.05) were significant factors that influenced achievement in mathematics. Based on findings, it is recommended that institutions should inisist students obtain the required minimum UTME scores becauser it will go a long way in supporting them to achieve greater performance in their intended courses of study at the higher level.